1997
DOI: 10.1093/jnci/89.22.1706
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein Expression: Critical Determinant in the Response to Osteosarcoma Chemotherapy

Abstract: P-glycoprotein expression does correlate with treatment failure in patients with osteosarcoma. This correlation raises the possibility that inhibiting the action of P-glycoprotein as part of therapy for this disease would improve outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
56
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(67 citation statements)
references
References 43 publications
8
56
0
3
Order By: Relevance
“…Heterogeneity for disease progression was driven in particular by two studies with opposing results. Chan et al 12 described a very impressive correlation between Pgp and clinical disease progression. Conversely, Wunder et al 7 found no such association in the largest study conducted to date, but their CIs suggest that a modest association with disease progression could not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneity for disease progression was driven in particular by two studies with opposing results. Chan et al 12 described a very impressive correlation between Pgp and clinical disease progression. Conversely, Wunder et al 7 found no such association in the largest study conducted to date, but their CIs suggest that a modest association with disease progression could not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have tried to investigate the role of Pgp in osteosarcoma, but the overall results remain controversial. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Single studies are limited unavoidably in terms of sample size, even when multicenter efforts are undertaken. However, the total accumulated data provide a considerable body of evidence.…”
mentioning
confidence: 99%
“…Certainly, the protein is endogenously expressed in a variety of tumours (for a review see Goldstein, 1996). Furthermore, the expression is frequently induced or upregulated following chemotherapy particularly in breast and the gastrointestinal tract (Schneider et al, 1989;Ro et al, 1990;Chan et al, 1991Chan et al, , 1997Pirker et al, 1993;Tokunaga et al, 2001;Coley et al, 2002).…”
mentioning
confidence: 99%
“…Although resistance to doxorubicin in human tumor cells may be caused by different mechanisms, including increased efflux, more efficient intracellular detoxification, alterations of topo-isomerase II and increased DNA repair, the most relevant mechanism of doxorubicin resistance in OSA has been demonstrated to be the ATP-binding cassette (ABC) transporters mediated drug efflux (Chou et al, 2006). In particular, high expression of ABCB1 protein (also known as MDR1 or P-glycoprotein) has bee n demonstrated to be responsible for doxorubicin resistance in human OSA cell lines and to be associated with an adverse clinical outcome in high-grade, non-metastatic OSA patients treated with conventional chemotherapy protocols (Baldini et al, 1995;Chan et al, 1997;Pakos et al, 2003;Serra et al, 2003). However, a few studies did not confirm this evidence (Gorlick et al, 1999;Schwartz et al, 2007) and have been recently discussed (Serra et al, 2007).…”
Section: Mechanisms Of the Chemotherapy Resistance By Abcb1 To Doxorumentioning
confidence: 99%